Forty Years After Chernobyl: Radiocaesium in Wild Edible Mushrooms from North-Eastern Poland and Its Relevance for Dietary Exposure and Food Safety - Iwona Mirończuk-Chodakowska; Jacek Kapała; Karolina Kujawowicz; Monika Sejbuk; Anna Maria Witkowska (Toxics, 2025)
Wild-growing edible mushrooms are known to bioaccumulate radionuclides from their environment, particularly the natural isotope potassium-40 (40K) and anthropogenic cesium-137 (137Cs). However, region-specific data for commercially relevant species in north-eastern Poland remain limited, despite the cultural and economic importance of mushroom foraging and export. This study aimed to assess the radiological safety of wild mushrooms intended for human consumption, with particular attention to regulatory compliance and potential exposure levels. In this study, 230 mushroom samples representing 19 wild edible species were analyzed using gamma spectrometry, alongside composite soil samples collected from corresponding foraging sites. The activity concentration of 137Cs in mushrooms ranged from 0.94 to 159.0 Bq/kg fresh mass (f.m.), and that of 40K from 64.4 to 150.2 Bq/kg f.m. None of the samples exceeded the regulatory limit of 1250 Bq/kg f.m. for 137Cs. The highest estimated annual effective dose was 2.32 µSv from 137Cs and 0.93 µSv from 40K, with no exceedance of regulatory limits observed in any sample. A strong positive correlation was observed between 137Cs activity in soil and mushroom dry mass (Spearman’s Rho = 0.81, p = 0.042), supporting predictable transfer patterns. Additionally, the implications of mushroom drying were assessed considering Council Regulation (Euratom) 2016/52, which mandates radionuclide levels in dried products be evaluated based on their reconstituted form. After such adjustment, even the most contaminated dried samples were found to comply with food safety limits. These findings confirm the radiological safety of wild mushrooms from north-eastern Poland and contribute novel data for a region with limited prior monitoring, in the context of current food safety regulations.